The effect of rising e-cigarette usage among young people on public health and physical activity - Mariusz Krompiewski; Marek Miśkiewicz; Jakub Ptak; Rafał Noga; Jagoda Marcinkowska; Adrian Herc; Karolina Koczkodon; Victoria Teska; Jakub Perłowski; Marcelina Sawczuk (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Electronic cigarettes (e-cigarettes/ENDS) are regarded by many as a safe alternative to traditional cigarettes. This article will present a review of the current knowledge regarding the effects and impact of electronic cigarettes on health and the risk of addiction in adolescents. Methods: We selected articles with an unlimited search period in several databases, including PubMed, Google Scholar, Web of Science and the websites of the Polish government. Only articles with free full text were included in the review. There were no restrictions based on article type. Conclusions: The increasing consumption of e-cigarettes (ENDS) among young people in Poland is emerging as a significant public health concern. The high addictive potential of nicotine, coupled with the toxicity of aerosols and the multitude of ways in which manufacturers make their products more appealing, gives rise to the risk of an increase in future patients with impaired performance in sports, and consequently with cardiovascular and respiratory diseases, as well as the necessity to combat addiction. Reducing and preventing the use of tobacco products by children and adolescents represents one of the most significant challenges currently facing the public health sector in Poland.